If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7 = 2x + -6 Reorder the terms: -7 + 5x = 2x + -6 Reorder the terms: -7 + 5x = -6 + 2x Solving -7 + 5x = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -7 + 5x + -2x = -6 + 2x + -2x Combine like terms: 5x + -2x = 3x -7 + 3x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 -7 + 3x = -6 + 0 -7 + 3x = -6 Add '7' to each side of the equation. -7 + 7 + 3x = -6 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = -6 + 7 3x = -6 + 7 Combine like terms: -6 + 7 = 1 3x = 1 Divide each side by '3'. x = 0.3333333333 Simplifying x = 0.3333333333
| 7x+14=28 | | 6y+18=24 | | 12x+1=91-6x | | 27x-4=122+6x | | 4y-12=20 | | x^3-6x^2-36x-40=0 | | 22x-7=209-2x | | 7a-14=21 | | 4x-8=52-2x | | 7a+14=21 | | 14x-7=213-8x | | 3x+4y=-3 | | 8x+1=121-4x | | 14x-4=12-2x | | x-4/7=3/7 | | -3.5=m-2.5 | | 4a+13=21 | | 3*x^3-9*x^2-9x+26=0 | | 4t-3.5t=1 | | n+7=28 | | -(2x-6)+(-x+7)=7 | | 3p^2+3p-60= | | x^2-3x+2=6 | | 2(4t-1)-4(1-t)=12t-6 | | 7x+13x-3x+1=2x | | 3p^2-10p+8=0 | | 2*+7=13 | | 3x+34=44+4x | | 3x+34=44+3x | | 3x+34=44+3s | | 6(n+1)=16 | | 6x-7=x-2 |